Antropopresja na środowisko państw europejskich - Sej-Kolasa, Małgorzata; Sztemberg-Lewandowska, Mirosława (Anthropogenic Impact on the European Environment, 2009)
The article analyzes changes in the anthropogenic impact on the environment across the European countries. The anthropogenic factor analyzed in the paper was air pollution. The analysis covered a selection of 16 indices describing the environmental impact recorded in each European country for eight subsequent periods. The analysis of time-based changes in index values was based on the growth curve model. First, a regression model was built for each European country to analyze the time changes of each index value. Then, a latent growth curve model was built. The model is based on the assumption that a change is a continuous process that can be described with variables whose realizations vary among objects. This approach to the change analysis allows the application of structural equation model for the analysis of latent growth curves.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 93-103